BIOCHEMICAL AND CLINICAL ASSESSMENT OF THYROID STATUS IN PATIENTS WITH THYROID DISORDERS REFERRED TO EL-OBIED REGIONAL HEALTH LABORATORY - Mohammed Eltayeb, Majdolin; Hassan Daoud, Omer; Ajabeldour, Ahmed Abdalla Ajabeldour; Eltahir Khalid, Khalid (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
Objective of this study: This study aimed at assessing the thyroid status in Kordofan region (western Sudan) where the prevalence of goitre was not clearly defined. Material and Methods : A cross-sectional, prospective study was conducted in Elobied regional health laboratory on 150 thyroid patients (136 female, 14 male) referred during the period between May-November 2003, their ages ranged between 6 to 65 years. A matching control group of 50 subjects (39 female, 11 male) without symptoms or signs of thyroid disease, were included for comparison. After clinical evaluation and data collection through a questionnaire, serum concentrations of TSH, total triiodothyronine (TT3), and total thyroxine (TT4) were measured by radioimmunoassay. Results: The frequency of thyroid disorders was higher in females (90.7%) than in males (9.3%), among the age group between 25-34 years. The percentage of patients with euthyroid was significantly higher (62%) compared with 28.3% of hyper and 9.3% of hypothyroidism. 69.3% of the thyroid patients had stage ІІ goitre. TT4, TT3 and TSH showed significant differences (P<0.001) in hyper and hypothyroidism compared with the euthyroid patients and the control group. Serum TT 4 values correlated negatively with TSH (r = 0.272, P = 0.001), and positively with TT 3 (r = 0.693, P = 0.000). Conclusion: The prevalence of thyroid diseases was found higher in this area, with strong association with the food intake and genetic background, a problem needing to be considered seriously.